Solitary Neurofibroma of the Floor of the Mouth: A Case Report - Motoyoshi Maruyama; Hiroaki Fushiki; Yukio Watanabe (Case Reports in Otolaryngology)
We present a case of a solitary neurofibroma of the floor of the mouth protruding into the submandibular region. A 51-year-old female presented with a 2-year history of swelling of the floor of the mouth. MRI revealed that the mass measuring 50×70 mm showed a homogenous, low signal intensity on a T1-weighted image and high signal intensity on a T2-weighted image. The tumor was completely removed through a cervical approach. Cases of a solitary neurofibroma originating from the floor of the mouth are extremely rare.